Northwest History. Alaska. Feature Articles. (1936)
Finds No Cannibals In Alaskan Search: Dr. F. G. Rainey Believes Legend Of Men With Tails Is Only A Story -- Discovers Flint Tools. FINDS NO CANNIBALS IN ALASKAN SEARCH Dr. F. G. Rainey Believes Legend of Men With Tails Is Only a Story—Discovers Flint Tools. FAIRBANKS, Alaska, Aug. 29 (/P).—Dr. Froelich G. Rainey of the University of Alaska, who went hunting for cannibals with tails, was back home tonight with a handful of flint and a belief that the legend of the tailed men is just a But the anthropologist and his aides from the American Museum of Natural history considered the primitive flint tools of prime importance. Dr. Rainey, who has done research in Haiti and the Philippines, first encountered the legend at the old Indian settlement, Batzulnetas, on the Abesna road, in the Tanana Crossing district of Alaska. "Chief Charley informed us strange, manlike beings called Tcet-tin lived in ancent times, in holes in the ground, and that they wore no clothes and had tails. "For some time these creatures captured lone Indians, killed and ate them, but eventually the Indians, taking them by surprise, burned them all in their holes. "In proof, we were shown some thirty dugouts on the bank of an old stream bed about half a mile from Batzulnetas. These dugouts are small—some no larger than four by six feet—and it may be that they are old fish caches. Others are big enough to have been small subterranean houses." Since the Indians asserted that their ancestors had no flint, and ascribed the tools to Tcet-tin, Dr. Rainey considered the implements of particular interest. "The persistence of the Tcet-tin legend may be peculiarly significant," he said. "Stories of people with tails are common among primitive peoples. It has been explained by the fact some arctic peoples wore parkas with a long tail or shirt down the back, which gave rise to the idea that these covered actual tails."